Stories of hope created together: A pilot, school-based workshop for sharing eco-emotions and creating an actively hopeful vision of the future - Marks, Elizabeth; Atkins, Ed; Garrett, Joanne K.; Abrams, Jesse F.; Shackleton, David; Hennessy, Lauren; Mayall, Elouise E.; Bennett, James; Leach, Isabel (Frontiers in Psychology, 2023)
The climate and ecological crises challenge all communities across the world, and the immost vulnerable and youngest are most affected. There are multiple impacts on mental health, including the psychological burdens that arise with increasing awareness of loss, threat and injustices. Large numbers of young people globally are understandably concerned and distressed about these crises, whilst simultaneously reporting that their concerns are regularly dismissed and ignored, particularly by those in power. This can increase feelings of isolation and distress, particularly if they have no recourse to effect change. This pilot project sought to explore how a schools-based, co-created workshop for school pupils aged 16 to 18 years could use a community-oriented space to explore their eco-emotions, address feelings of isolation and engender a sense of realistic, active hope, using storytelling and images of possible futures. A three-hour workshop for delivery in schools was co-designed with young people, researchers, educators and clinicians, using principles of Youth Participatory Action Research (YPAR). Six school pupils consented and four completed the workshop, which involved a range of group-based activities to explore their understanding of the climate and ecological crises, support emotional expression related to these and engage in storytelling about hopeful and realistic futures. A live illustrator in attendance created shared images of the participant'’s fears and hopes. The workshop was recorded, transcribed and analysed using Thematic Analysis and sentiment analysis. Feedback was sought from participants at one and four weeks after completion and analysed using content analysis. Results indicated that participants reported a range of painful and positive emotions about the crises. They highly valued having space to express their experience alongside others. Storytelling and creativity appeared to help them articulate their feelings and hopes for the future, and gave them greater motivation and confidence in talking to others about these topics. This innovative pilot study suggests that a school-based youth participatory group could offer a novel way of helping children and young people to engage more with the climate and ecological crises in a way that supports their wellbeing. It provides strong support for future, larger-scale projects in this area.